Exploring the antioxidant and protective effects of Marsdenia thyrsiflora Hook.f. leaf extract against carbon tetrachloride-induced hepatic damage in rat models - Saha, Sushmita; Alshammari, Abdulrahman; Albekairi, Norah A.; Zulfiquar, Tasniya Nahiyan; Shakil, Md Salman; Mondal, Kakoli Rani; Kundu, Milton Kumar; Mondal, Milon; Mubarak, Mohammad S. (Frontiers in Pharmacology, 2024)
The study significantly contributes to the field by elucidating the potent antioxidant and hepatoprotective properties of Marsdenia thyrsiflora leaf extract against carbon tetrachloride (CCl4)induced hepatic damage in rat models for the first time. This research highlights M. thyrsiflora methanolic leaf (MTLM) extract's rich phenolic and flavonoid content, effectively neutralizing harmful free radicals and enhancing the liver's antioxidant defenses. The study demonstrates the MTLM's ability to mitigate liver injury by reducing lipid peroxidation and normalizing key liver enzymes such as ALT, AST, and ALP through comprehensive biochemical and histopathological analyses. Additionally, MTLM improves serum lipid profiles, indicating a broader metabolic benefit. This investigation pioneers the exploration of M. thyrsiflora's medicinal potential, providing a scientific basis for its traditional use in treating liver disorders. The findings suggest that MTLM could be developed as a natural therapeutic agent to counteract liver toxicity and oxidative stress. By bridging the gap between traditional medicine and modern pharmacological research, this study opens avenues for further exploration into the safety, efficacy, and active constituents of M. thyrsiflora, offering a promising alternative for managing liver diseases and oxidative stress-related conditions.